Emotion recognition in autism spectrum disorder across age groups: A cross‐sectional investigation of various visual and auditory communicative domains. Issue 4 (2nd February 2023) - Leung, Florence Y. N.; Stojanovik, Vesna; Micai, Martina; Jiang, Cunmei; Liu, Fang
Abstract: Previous research on emotion processing in autism spectrum disorder (ASD) has predominantly focused on human faces and speech prosody, with little attention paid to other domains such as nonhuman faces and music. In addition, emotion processing in different domains was often examined in separate studies, making it challenging to evaluate whether emotion recognition difficulties in ASD generalize across domains and age cohorts. The present study investigated: (i) the recognition of basic emotions (angry, scared, happy, and sad) across four domains (human faces, face‐like objects, speech prosody, and song) in 38 autistic and 38 neurotypical (NT) children, adolescents, and adults in a forced‐choice labeling task, and (ii) the impact of pitch and visual processing profiles on this ability. Results showed similar recognition accuracy between the ASD and NT groups across age groups for all domains and emotion types, although processing speed was slower in the ASD compared to the NT group. Age‐related differences were seen in both groups, which varied by emotion, domain, and performance index. Visual processing style was associated with facial emotion recognition speed and pitch perception ability with auditory emotion recognition in the NT group but not in the ASD group. These findings suggest that autistic individuals may employ different emotion processing strategies compared to NT individuals, and that emotion recognition difficulties as manifested by slower response times may result from a generalized, rather than a domain‐specific underlying mechanism that governs emotion recognition processes across domains in ASD. Lay summary: Autistic individuals often have difficulties with recognizing emotions, but it is unclear whether this is the case for different age cohorts and across different stimulus domains. We examined recognition of emotions from human faces, face‐like objects, speech, and song in 38 autistic and 38 non‐autistic children, adolescents, and adults. Our results showed that autistic individuals recognized emotions as accurately as non‐autistic individuals across all domains and ages. However, they were slower than non‐autistic individuals in recognizing emotions and might use different strategies during this process.